2021
DOI: 10.18203/2320-1770.ijrcog20210296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of non-descent vaginal hysterectomy and laparoscopy assisted vaginal hysterectomy

Abstract: Background: We aimed to assess and compare intra operative and post-operative parameters and complications associated with non-descent vaginal hysterectomy group (NDVH) and laparoscopic assisted vaginal hysterectomy group (LAVH).Methods: In this observational study 100 patients with uterine size not exceeding 12 weeks of gravid uterus, adequate uterine mobility, fibroid uterus, dysfunctional uterine bleeding, chronic cervicitis, adenomyosis and post-menopausal bleeding were divided into two groups to undergo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…In this study most of the patients for surgery happened to be of the common age group of 41 to 50 years and similar was noticed by Chang well. 3,4,10 The average parity happened to be 3 in LAVH group whereas in NDLH it was 2, which commensurates with the respective groups of the study conducted by Goswami et al and Shiragur et al 6,9 In this study, most common cause to force surgery in these two groups (LAVH 28.8% and 26.9% NDVH) were fibroid uterus of size 12-14 weeks or less, followed by adenomyosis (23.1% LAVH and 26.9% NDVH ) which is in sync with the study conducted by Shiragur et al 9 Whereas Goswami et al observed leiomyoma as the most prevalent indication for LAVH (32.5%) and AUB for the NDVH group (37.9%). 7 Despite the same team of surgeon performing both the procedures, the average period of surgery in NDVH in the absence of debulking was 90.54±5.89 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study most of the patients for surgery happened to be of the common age group of 41 to 50 years and similar was noticed by Chang well. 3,4,10 The average parity happened to be 3 in LAVH group whereas in NDLH it was 2, which commensurates with the respective groups of the study conducted by Goswami et al and Shiragur et al 6,9 In this study, most common cause to force surgery in these two groups (LAVH 28.8% and 26.9% NDVH) were fibroid uterus of size 12-14 weeks or less, followed by adenomyosis (23.1% LAVH and 26.9% NDVH ) which is in sync with the study conducted by Shiragur et al 9 Whereas Goswami et al observed leiomyoma as the most prevalent indication for LAVH (32.5%) and AUB for the NDVH group (37.9%). 7 Despite the same team of surgeon performing both the procedures, the average period of surgery in NDVH in the absence of debulking was 90.54±5.89 min.…”
Section: Discussionmentioning
confidence: 99%
“…Soren et al reported a period of 65.44 min and that of Shiragur et al was100-200 min 10. For LAVH group the mean duration was 127.12±12.58 min which was comparatively longer than NDVH.…”
mentioning
confidence: 82%